Geography, private costs and uptake of screening for abdominal aortic aneurysm in a remote rural area - Cairns John; Duncan John L; Lindsay Sandra M; Godden David J (BMC, 2006)
Abstract Background The relationship between geographical location, private costs, health provider costs and uptake of health screening is unclear. This paper examines these relationships in a screening programme for abdominal aortic aneurysm in the Highlands and Western Isles of Scotland, a rural and remote area of over 10,000 square miles. Methods Men aged 65-74 (n = 9323) were invited to attend screening at 51 locations in 50 settlements. Effects of geography, deprivation and age on uptake were examined. Among 8,355 attendees, 8,292 completed a questionnaire detailing mode of travel and costs incurred, time travelled, whether accompanied, whether dependants were cared for, and what they would have been doing if not attending screening, thus allowing private costs to be calculated. Health provider (NHS) costs were also determined. Data were analysed by deprivation categories, using the Scottish Indices of Deprivation (2003), and by settlement type ranging from urban to very remote rural. Results Uptake of screening was high in all settlement types (mean 89.6%, range 87.4 - 92.6%). Non-attendees were more deprived in terms of income, employment, education and health but there was no significant difference between non-attendees and attendees in terms of geographical access to services. Age was similar in both groups. The highest private costs (median £7.29 per man) and NHS screening costs (£18.27 per man invited) were observed in very remote rural areas. Corresponding values for all subjects were: private cost £4.34 and NHS cost £15.72 per man invited. Conclusion Uptake of screening for abdominal aortic aneurysm in this remote and rural setting was high in comparison with previous studies, and this applied across all settlement types. Geographical location did not affect uptake, most likely due to the outreach approach adopted. Private and NHS costs were highest in very remote settings but still compared favourably with other published studies.